2018
DOI: 10.1021/acsami.8b15049
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and Efficient Capture of Inorganic Nitrogen and Heavy Metals by Polyporous Layered Double Hydroxide and Biochar Composite for Agricultural Nonpoint Pollution Control

Abstract: Agricultural nonpoint pollution has been recognized as the main source of aquatic contaminants worldwide, such as inorganic nitrogen (ION) and heavy metals (HMs). It is an important challenge to simultaneously and efficiently immobilize soil ION and HMs in farmland. Herein, we present a polyporous Mg/Fe-layered double hydroxide and biochar composite (Mg/Fe-LDH@biochar) with the efficient coadsorption capacity of ION and HMs for the mitigation of agricultural nonpoint pollution toward aquatic systems. The Mg/Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 69 publications
3
31
0
Order By: Relevance
“…Moreover, the existence of the (003) peak confirms that the samples still preserve their layered morphology in the range of pH values tested. Such results indicate that the Mg–Fe LDH shows high chemical stability over a wide range of pH values which is in agreement adsorbent chemical stability with previously reported results (Zhang et al , 2018). Also, the chemical stability of prepared adsorbents was examined by determining the leaching percentage of magnesium in solution at different initial pH = 2.5–12.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, the existence of the (003) peak confirms that the samples still preserve their layered morphology in the range of pH values tested. Such results indicate that the Mg–Fe LDH shows high chemical stability over a wide range of pH values which is in agreement adsorbent chemical stability with previously reported results (Zhang et al , 2018). Also, the chemical stability of prepared adsorbents was examined by determining the leaching percentage of magnesium in solution at different initial pH = 2.5–12.…”
Section: Resultssupporting
confidence: 93%
“…According to the proposed circular plan of agricultural waste utilization, plant residues, animal manures, and food wastes are recycled to produce engineered biochar are specifically designed for treating the wastewater generated from agricultural and domestic sources. At the same time, biochar can be applied to agricultural fields as a soil amendment to improve WUE [136], remediate diffuse-source contamination [137], and/or improve crop yields [48]; it can also be used as a clean fuel for energy supply (heading value >23 MJ/kg) [138,139]. It has been reported that the addition of biochar to soil could often enhance the plant available water (PAW) and WUE, although the soil type played an important role on the influence [140].…”
Section: Multidimensional Benefits In Circular Agriculturementioning
confidence: 99%
“…In a search for the most desired and efficient remediation material for cobalt, biochar should be considered. Due to the presence of a highly-porous structure [13], various functional groups (e.g., carboxyl, hydroxyl, and phenolic groups) [14] on biochar show a great affinity for metal cations [15]. The composition and biochar stability establish the sorption properties of the material.…”
Section: Introductionmentioning
confidence: 99%